Study on Health-Related Quality of Life in Bone Cancer Patients - Cheah, W.L; Soh, Mei Hua; Chang, C.T (Researchman Publishers, 2013)
Background and Objectives : Like any other cancers treatment, bone cancer patients undergo pain and suffering that may compromise their functional status, ability to adjust and subsequently quality of life. This study aimed to investigate the impact of bone cancer on quality of life among bone cancer patients. Materials : This cross-sectional study was conducted at Sarawak General Hospital, Kuching, Sarawak. Bone cancer patients were interviewed using a pretested 30-item questionnaire adopted from EORTC (European Organization for Research and Treatment of Cancer). Data was analysed using SPSS software. Results : A total of 50 respondents was recruited during the two months data collection. Majority of the patients are aged 40 years and below, 54% were females, 28% were Malays, 60% were married. Majority of the respondents were studying or working, 54% had education up to secondary level and higher. The mean QoL score for global health status was 53.8 ± 14.6. The highest score on the functional scale was for Physical functioning (71.0 ± 20.5), followed by Cognitive functioning (70.3 ± 27.2). Under Symptom scales, the highest score was Financial difficulties (64.6 ± 28.0), followed by Appetite loss (51.3 ± 25.3), Insomnia (50.6 ± 23.5), and others with Dyspnoea having the lowest mean score (5.66 ± 9.88). Conclusion : Overall bone cancer patients perceived their quality of life to be lower. Sustained problems such as emotional functioning, social functioning, nausea and vomiting, appetite loss and financial difficulties were observed. Appropriate interventional programmes should be designed to help these patients to improve their overall quality of life.